Artificial Intelligence (AI)-Assisted Hybrid Learning For Improved Learning Outcomes on Digital Literacy Problems - Palayukan, Hersiyati; Triyani, Septi; Palengka, Inelsi (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2024)
Hybrid learning, also known as blended learning, is a learning approach that combines traditional face-to-face learning with online learning. This research uses a qualitative research type with a descriptive approach. the research subjects were taken students of the education study program at the Indonesian Christian University of Toraja in the fourth semester. The preliminary research used a random interview method to obtain preliminary data on the application of artificial intelligence. The conclusions that can be drawn from the data and discussions above are that hybrid learning with artificial intelligence (AI) can improve student learning outcomes. However, there are obstacles and challenges that students face. The obstacles that arise are related to the need to be able to keep up with technological developments by using and utilizing AI appropriately and well. These obstacles and challenges are related to how to.